The Influence of Community Involvement on the Success of Road and Canal Projects in the Slum Quality Improvement Program by Mediating Satisfaction and Communication Quality in Tanjung Priok District, North Jakarta - Agung Suparjono; Mawardi Amin (Eduvest - Journal of Universal Studies, 2026)
The issue of slum areas in North Jakarta poses a significant challenge that requires serious attention. The Community Implementation Project (CIP) program has emerged as a solution to improve the quality of slum settlements through active community involvement. It is believed that community participation can enhance the success of infrastructure development projects, particularly in terms of quality, sustainability, and long-term maintenance. This study aims to analyze the influence of community involvement on the success of infrastructure projects in slum areas of North Jakarta, with community satisfaction as a mediating variable and government support as a moderating variable. A quantitative research approach is employed, using a survey that involves respondents from six districts in North Jakarta that participate in the CIP program. Data collected through questionnaires will be analyzed using the Structural Equation Modelling–Partial Least Squares (SEM–PLS) method to identify the relationships between variables. The findings of this study are expected to demonstrate that community involvement contributes significantly to project success. Government support is anticipated to strengthen the relationship between community involvement and project outcomes, while community satisfaction may act as a mediator that enhances the effect of participation on project performance.